2015
DOI: 10.1002/anie.201508339
|View full text |Cite
|
Sign up to set email alerts
|

Systemically Injectable Enzyme‐Loaded Polyion Complex Vesicles as In Vivo Nanoreactors Functioning in Tumors

Abstract: The design and construction of nanoreactors are important for biomedical applications of enzymes, but lipid- and polymeric-vesicle-based nanoreactors have some practical limitations. We have succeeded in preparing enzyme-loaded polyion complex vesicles (PICsomes) through a facile protein-loading method. The preservation of enzyme activity was confirmed even after cross-linking of the PICsomes. The cross-linked β-galactosidase-loaded PICsomes (β-gal@PICsomes) selectively accumulated in the tumor tissue of mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
147
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 37 publications
3
147
1
1
Order By: Relevance
“…Therefore, PICsomes can provide an ideal compartment for enzymes. In particular, we reported that there was no reduction in the enzyme activity of a β‐galactosidase‐loaded PICsome with a diameter of 100 nm; we demonstrated that the PICsome‐based nanoreactor was systemically injectable into mice and worked for tumor imaging under in vivo conditions . However, the influence of physicochemical parameters on enzymes loaded in the inner aqueous phase of PICsomes is still unknown.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Therefore, PICsomes can provide an ideal compartment for enzymes. In particular, we reported that there was no reduction in the enzyme activity of a β‐galactosidase‐loaded PICsome with a diameter of 100 nm; we demonstrated that the PICsome‐based nanoreactor was systemically injectable into mice and worked for tumor imaging under in vivo conditions . However, the influence of physicochemical parameters on enzymes loaded in the inner aqueous phase of PICsomes is still unknown.…”
Section: Introductionmentioning
confidence: 90%
“…Thus, the development of more versatile and advanced “engineered” platforms is desired for future enzyme applications. Previously, we focused on the polymeric vesicle “PICsome” for encapsulating enzymes . PICsomes are characterized by a facile preparation method, that is, a simple mixing of polymers and enzymes, which results in encapsulation of enzymes into their inner aqueous phase without the loss of enzyme activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] More seriously,t he non-specific distribution also leads to undesirable systemic toxicity. [7] Meanwhile,m etalorganic frameworks, [8] polymers, [9] and other carriers [10] have been developed to solve the problems of high instability and rapid degradation of the exogenous enzymes in vivo. [7] Meanwhile,m etalorganic frameworks, [8] polymers, [9] and other carriers [10] have been developed to solve the problems of high instability and rapid degradation of the exogenous enzymes in vivo.…”
mentioning
confidence: 99%
“…[6] When the latter form closed shells,they are called vesicles,or, for polymers,"polymersomes". [9] In principle,w ee xpect to also find the various morphologies in this case,b ut, surprisingly,l amellar morphologies turn out to be rare.T he only case known to date are the so-called "PICsomes" (PIC = polyion complex) reported by Kataoka and co-workers in as eries of papers, [10] wherein carefully length-matched pairs of charged blocks of varying chemistry were chosen. [8] Here,t he driving force for assembly is not poor solubility of hydrophobic components,but complex formation between negative and positive chains,leading to an insoluble (micro) phase that forms the core of the assembly.A neutral (hydrophilic) block is required to form the corona.…”
mentioning
confidence: 99%